A study of nutritional anemia among urban primary school children of Katihar - Pandey, Arun Kumar; Rani, Soni (International Journal Of Community Medicine And Public Health, 2019)
Background: Children health is an important concern for all societies since it contributes to overall development. The present position with regards to health and nutritional status of children is not satisfactory despite of mid-day meal programme running in government run schools. This study is conducted to assess the proportion of children, aged between 6 year to 11 years having anemia and socio demographic factors associated with iron deficiency anemia among selected children. Methods: For the purpose of study a list of all government primary schools of Katihar had been prepared and equal numbers of students were examined from randomly selected schools. By taking the prevalence of anemia 50% among school children for confidence level 95% with 10% relative precision with sample size comes out to be 384. The sample size was doubled to cover both boys and girls in the study. A total of 800 students (426 boys and 374 girls) in the age group of 6-11 years were interviewed and examined. Results: Out of 800 children total 343 (42.88%) were anemic. The prevalence of anemia was 37.96% among boys and 48.07% among girls. The prevalence of mild and moderate anemia among boys was 32.05% and 67.95% and 70.8% and 29.2% among girls respectively. The prevalence of anemia was high among lower and upper lower socio-economic status (100% and 45.32%). The proportion of anemic children showed a significant association with education of mother and nutritional status. Proportion of anemia decreased significantly with increase in education status of mother. Conclusions: The prevalence of anemia was found high among primary school children. Major factors which influence the prevalence of anemia were socioeconomic status, mother education and nutritional status of children.